Optogenetically induced olfactory stimulation in Drosophila larvae reveales the neuronal basis of odor-aversion behavior - Bellmann, Dennis; Richardt, Arnd; Freyberger, Robert; Nuwal, Nidhi; Schwärzel, Martin; Fiala, André; Störtkuhl, Klemens F. (Frontiers in Behavioral Neuroscience, 2010)
Olfactory stimulation induces an odor-guided crawling behavior of Drosophila melanogaster larvae characterized by either an attractive or a repellent reaction. In order to understand the underlying processes leading to these orientations we stimulated single olfactory receptor neurons (ORNs) through photo-activation within an intact neuronal network. Using the Gal4-UAS system two light inducible proteins, the light-sensitive cation channel channelrhodopsin-2 (ChR-2) or the light-sensitive adenylyl cyclase (Pac α) were expressed in all or in individual ORNs of the larval olfactory system. Blue light stimulation caused an activation of these neurons, ultimately producing the illusion of an odor stimulus. Larvae were tested in a phototaxis assay for their orientation towards or away from the light source. Here we show that activation of Pacα expressing ORNs bearing the receptors Or33b or Or45a in blind norpA mutant larvae induces a repellent behavior away from the light. Conversely, photo-activation of the majority of ORNs induces attraction towards the light. Interestingly, in wild type larvae two ligands of Or33b and Or45a, octyl acetate and propionic ethylester, respectively, have been found to cause an escape reaction. Therefore, we combined light and odor stimulation to analyze the function of Or33b and Or45a expressing ORNs. We show that the larval olfactory system contains a designated neuronal pathway for repellent odorants and that activation of a specific class of ORNs already determines olfactory avoidance behavior.